Identification and molecular characterization of a novel sugarcane streak mastrevirus and an isolate of the A-strain of maize streak virus from sugarcane in Nigeria - Yahaya, A.; Dangora, D.B.; Alegbejo, M.D.; Kumar, P. Lava; Alabi, O.J. (Springer, 2017)
Sugarcane and maize plants showing symptoms typical of those described for the so-called “African streak viruses” (AfSVs) were encountered during field surveys conducted from February to July 2015 to document viruses infecting both crops across the northern Guinea savannah region of Nigeria. As part of this study, two categories of complete mastrevirus-like genome sequences were obtained from nine samples (maize = 2; sugarcane = 7). In pairwise comparisons, the full-length genomes of the first sequence category (2,687 nt each; maize = 2; sugarcane = 2) shared 96 to 99% identity with global isolates of the A-strain of maize streak virus (MSV-A), indicating that sugarcane may also serve as a reservoir host to MSV-A. Analysis of the complete genomes belonging to the second sequence category (2,757 nt each; sugarcane = 5) showed that they shared 42 to 67% identity with their closest AfSV relatives, thus indicating that they represent sequences of a novel mastrevirus. Both sequence categories shared 61-62% sequence identity with each other. Further analysis revealed that the novel sugarcane-infecting virus, tentatively named as sugarcane chlorotic streak virus (SCSV), arose from a putative interspecific recombination event involving two grass-infecting mastreviruses, eragrostis streak virus and urochloa streak virus, as putative parental sequences. The results of this study add to the repertoire of diverse AfSVs present in cereal and sugarcane mixed cropping landscapes in the northern Guinea savannah region of Nigeria, with implications for disease epidemiology.